Corals differential susceptibilities to bleaching along the Red Sea Coast, Egypt - MOHAMMED S. A. AMMAR; AHMED HAMED OBUID-ALLAH; MONTASER A. M. AL-HAMMADY (Nusantara Bioscience, 2011)
Abstract. Ammar MSA, Obuid-Allah AH, Al-Hammady MAM. 2011. Corals differential susceptibilities to bleaching along the Red Sea Coast, Egypt. Nusantara Bioscience 3: 73-81. Coral bleaching was studied at four sites in four widely geographically separated areas. Three of these sites are subjected to different human activities and the fourth one is considered as a control site. Data were collected by using SCUBA diving, and the line transects method. A total of 3940 coral colonies, representing 62 species in 21genera and 10 families, were recorded on transects on the reefs of four studied sites.20.11% of all corals were affected by bleaching: 5.4% were moderately affected; 2.7% severely affected and 12.007% were dead. Overall, there were differences in the proportion of colonies affected by bleaching between the studied sites. Ras El-Behar, the site impacted by petroleum oil, has the maximum average proportion of moderately, severely bleached and dead colonies. While, the lowest average proportions of severely bleached colonies and dead colonies were found at Kalawy bay. Surprisingly, coral reef taxa at El-Hamraween harbor showed high resistance to bleaching probably because of having a new different clade of Symbiodinium which can withstand seawater temperature. Species with highest susceptibilities to bleaching in areas of oil pollution, increased sedimentation and heavy load of phosphate is Stylophora pistillata, Acropora granulosa, and Montipora meandrina, respectively while species with lowest susceptibilities are Fungia fungites, Alveopora daedalea and Millepora dichotoma, respectively.